2010
DOI: 10.1029/2009jd012157
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of precipitation over Indian land and oceanic regions by synergistic use of multisatellite sensors

Abstract: [1] In the present study, an attempt was made to estimate rainfall by synergistically analyzing collocated thermal infrared (TIR) brightness temperatures from Meteosat along with rainfall estimates from active microwave precipitation radar (PR) on the Tropical Rainfall Measuring Mission (TRMM) over Indian land and oceanic regions. In this study, we used broad and frequent TIR measurements from a geostationary satellite for rainfall estimation, calibrating them with sparse but more accurate PR rain rates. To ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…These results differ from the findings of Jamandre and Narisma [48] in the Philippines, who found that SPPs (in their case CMORPH and TRMM) performed better during the SWM. By contrast, Mishra et al [49], in India, showed that TRMM 3B42V6 had a lower RMSE, bias, and FAR for NEM compared to SWM. These differences may be explained by the origin of precipitation with convective weather systems (which dominate during the NEM) being more accurately detected by satellite sensors [50].…”
Section: Evaluation Of Seasonal Precipitationmentioning
confidence: 99%
“…These results differ from the findings of Jamandre and Narisma [48] in the Philippines, who found that SPPs (in their case CMORPH and TRMM) performed better during the SWM. By contrast, Mishra et al [49], in India, showed that TRMM 3B42V6 had a lower RMSE, bias, and FAR for NEM compared to SWM. These differences may be explained by the origin of precipitation with convective weather systems (which dominate during the NEM) being more accurately detected by satellite sensors [50].…”
Section: Evaluation Of Seasonal Precipitationmentioning
confidence: 99%
“…A large number of studies have evaluated the performance of 3V42V6 in many parts of world [11][12][13][14][15]. Although some studies have also documented the performance of 3B42V7 in different regions of the world [14][15][16][17][18], limited studies have reported on its performance relative to its predecessor (3B42V6) and near real time product (3B42RT) in complex terrain regions having cryospheric environment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a new algorithm, the Indian National Satellite System (INSAT) Multispectral Rainfall Algorithm (IMSRA), was developed which benefits from the high spatial and temporal resolutions of Kalpana-1 and more accurate rainfall data from TRMM-PR (Prakash et al, 2009;Gairola et al, 2010b). This algorithm also uses proper cloud classification schemes from TIR and water vapor channels of Kalpana-1 and the procedure is the same as the one used by Mishra et al (2010) for rainfall estimation by the Meteosat-First Generation satellite and TRMM-PR datasets. IMSRA is capable of estimating rainfall from Kalpana-1 satellite data at high spatial (0.25º latitude × 0.25º longitude) and temporal (3-hourly) resolutions.…”
Section: Introductionmentioning
confidence: 99%